The expression of nuclear factor of activated T cell c1 and receptor activator of nuclear factor kappa β induced by Enterococcus faecalis in osteoclastogenesis (laboratory experiment on Wistar rats) - Nirawati Pribadi; Rosita Rahmawati; Mandojo Rukmo; Adelina Kristanti Tandadjaja; Hendy Jaya Kurniawan; Ratna Puspita Hadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Enterococcus faecalis (E. faecalis) is the most common bacteria species in persistent endodontic infection of teeth undergoing root canal treatment at a prevalence of 38%. The virulence factor of this bacterium is Lipoteichoic acid (LTA) which can be recognized by Toll-like receptors-4 (TLR-4) that produce a stimulus and provoke an immune response. Inflammation results in bone defects that feature multiple cytokines and interactions between different cell types. Bone loss within a periapical tooth is characterized by osteoclast formation (osteoclastogenesis) in the bone. Purpose: This study aimed to determine the expression of nuclear factor of activated T cell c1 (NFATc1) and receptor activator of nuclear factor kappa β (RANK) which played a role in osteoclastogenesis at different time intervals. Methods: 36 upper molar teeth of the research subjects were induced with 106 CFU Enterococcus faecalis and subsequently observed for 7 and 21 days with the NFATc1 and RANK being counted microscopically at 1000X magnification across 20 viewing fields. Thereafter, the data was examined and analyzed by means of an independent T test using SPSS. Results: NFATc1 and RANK expression were higher in the group including E. faecalis on days 7 and 21 than in the control group. There were significant differences between the treatment group and control group with regard to NFATc1 and RANK expression (p<0.05). Conclusion: The study showed that the expression of NFATc1 and RANK, which plays a role in osteoclastogenesis, was higher in periapical bone defects in Wistar rats induced by E. faecalis than those which were not induced.